Leveraging Science, Technology and Innovation for National Development in the Light of the Emerging Universities of Science and Technology in Kenya - Amukowa, Wyclife O.; Ayuya, Caroline V. (My University, 2013)
It is recognized that effective leveraging of science, technology and innovation is essential for wealth creation in all nations. Science, Technology and Innovation is also a key component of social integration, sustainable development and poverty eradication based on equity, freedom, justice, governance, peace and prosperity. At the international level, science, technology and innovation act as a tool of international co-operation and solidarity. It is useful for provision of knowledge and information as well as facilitating globalization with human development while concomitantly strengthening national governance and acting as a vector of common heritage, international cooperation and solidarity. Appropriate Science, Technology and Innovation policy is key to the production, distribution and use of knowledge and information. This paper endeavours to underscore how the continued growth of universities of science and technology could steer Kenya’s economic growth among other priority areas as outlined by the government.
Keywords: Science & Technology; Education; Development; Employment; University